Evaluating the effectiveness of the influenza vaccine during respiratory outbreaks in Singapore's long term care facilities, 2017. Issue 29 (27th June 2019) - Ng, Yixiang; Nandar, Khine; Chua, Lily Ai Vee; Mak, Tze Minn; Foo, Kelly; Muhammad, Imran Roshan; Low, Constance Khia Ki; Ma, Stefan; Ooi, Steven Peng-Lim; Lin, Raymond Tzer Pin; James, Lyn; Lee, Vernon Jian Ming
Highlights: Influenza vaccine effectiveness (VE) was estimated using respiratory outbreak data. VE was estimated to reach as high as 67.9% against influenza A(H3N2). In contrast, estimated VE against influenza A(H1N1)pdm09 was only 35.4%. Higher effectiveness was also seen in individuals who were recently vaccinated. Our study provides novel data on influenza vaccine effectiveness in the tropics. Abstract: Influenza outbreaks occur periodically in Long Term Care Facilities (LTCFs) and vaccination is critical in preventing influenza infections. We evaluated the influenza vaccine effectiveness (VE) during respiratory outbreaks in LTCFs reported to the Ministry of Health, Singapore in 2017. A test-negative design was used to estimate the ratio of the odds of testing positive for influenza among vaccinated individuals to the odds among unvaccinated individuals. The VE was calculated as (1-odds ratio) × 100%. For adjusted VE, the estimates were derived using logistic regression adjusted for age group, gender, month of illness, and number of days from date of illness onset till to swab collection date. Estimates by influenza subtypes and post-vaccination time periods (15–180 days & 181–365 days) were also calculated using stratified data. 264 individuals, with 118 laboratory-confirmed influenza cases [32 A(H1N1)pdm09, 75 A(H3N2), 11 A(untypable)], were included in the analysis. No one was identified to be infected with influenza B. The overall adjusted VE estimate was 40.5% (95% CI: −12.2–68.5%), while the subtype-specific adjusted VE estimates were −43.4% (95% CI: −312.4–50.2%) against A(H1N1)pdm09 and 57.1% (95% CI: 5.7–80.5%) against A(H3N2). At 15–180 days post-vaccination period, the adjusted VEs were 59.3% (95% CI: 18.0–79.8%) against all influenza, 35.4% (95% CI: −123.5–81.3%) against A(H1N1)pdm09 and 67.9% (95% CI: 22.5–86.7%) against A(H3N2). Estimates were not significant at 181–365 days post-vaccination. The influenza vaccine showed varying effectiveness among individuals in Singapore's LTCFs in 2017, with a higher effectiveness among those who were more recently vaccinated. It remains an important tool in preventing influenza infections, especially for those who are at high risk of influenza-related complications.